Lipid peroxidation, antioxidant enzymes and glutathione levels in human erythrocytes exposed to colloidal iron hydroxide in vitro - Ferreira, A.L.A. [UNESP]; Machado, P.E.A. [UNESP]; Matsubara, L.S. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1999)
The free form of the iron ion is one of the strongest oxidizing agents in the cellular environment. The effect of iron at different concentrations (0, 1, 5, 10, 50, and 100 µM Fe3+) on the normal human red blood cell (RBC) antioxidant system was evaluated in vitro by measuring total (GSH) and oxidized (GSSG) glutathione levels, and superoxide dismutase (SOD), catalase, glutathione peroxidase (GSH-Px) and reductase (GSH-Rd) activities. Membrane lipid peroxidation was assessed by measuring thiobarbituric acid reactive substance (TBARS). The RBC were incubated with colloidal iron hydroxide and phosphate-buffered saline, pH 7.45, at 37oC, for 60 min. For each assay, the results for the control group were: a) GSH = 3.52 ± 0.27 µM/g Hb; b) GSSG = 0.17 ± 0.03 µM/g Hb; c) GSH-Px = 19.60 ± 1.96 IU/g Hb; d) GSH-Rd = 3.13 ± 0.17 IU/g Hb; e) catalase = 394.9 ± 22.8 IU/g Hb; f) SOD = 5981 ± 375 IU/g Hb. The addition of 1 to 100 µM Fe3+ had no effect on the parameters analyzed. No change in TBARS levels was detected at any of the iron concentrations studied. Oxidative stress, measured by GSH kinetics over time, occurs when the RBC are incubated with colloidal iron hydroxide at concentrations higher than 10 µM of Fe3+. Overall, these results show that the intact human RBC is prone to oxidative stress when exposed to Fe3+ and that the RBC has a potent antioxidant system that can minimize the potential damage caused by acute exposure to a colloidal iron hydroxide in vitro.
Keywords: catalase; superoxide dismutase; glutathione; iron; erythrocyte; thiobarbituric acid reactive substance